Discipleship from Catholic, mainline and conservative Protestant congregant perspectives in Canada. Issue 4 (2nd October 2022) - Wong, Arch Chee Keen; Thiessen, Joel; Walker, Keith; McAlpine, Bill
ABSTRACT: This article investigates discipleship in Canada, with a focus on spiritual and discipleship practices and processes that help to facilitate spiritual growth among congregants. The study draws on survey data from over 250 Catholic, mainline, and conservative Protestant congregations, with over 9100 participating congregants. The data shows how those in each denominational tradition understand the spiritual practices and discipleship processes that aid in their spiritual growth, and also reveals the importance of a congregational context that is welcoming, safe, and caring as precursors to effective discipleship. The Relational Spirituality model is used to explain the spiritual development of congregants' ways of relating to the sacred, drawing especially on two concepts: spiritual dwelling and spiritual seeking.